2019
DOI: 10.1108/md-04-2017-0383
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exchange volatility exposure on firms’ foreign-denominated debts

Abstract: Purpose This research began by acknowledging that conventional analysis on the foreign exchange exposure could not adequately reflect firms’ risk management strategies, which firms take actions against uncertainties raised by foreign exchange. In order to conceptualize uncertainty aroused by foreign exchange, the purpose of this paper is to develop an index that could measure corporate profits’ sensitivity to foreign exchange uncertainty and examine its possibility of utilization. Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…This was also confirmed by Choi and Choi (2018), who found that the devaluation of the RMB had a direct effect on reducing unemployment. Min and Yang (2019) looked at the problem of debt risks in a currency other than the domestic currency in South Korean companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was also confirmed by Choi and Choi (2018), who found that the devaluation of the RMB had a direct effect on reducing unemployment. Min and Yang (2019) looked at the problem of debt risks in a currency other than the domestic currency in South Korean companies.…”
Section: Literature Reviewmentioning
confidence: 99%